Pelatihan dan Perbaikan Website Sebagai Media Promosi Sarasvita FCJ Center - Rudolfo Rizki Damanik; Robin (Yayasan Literasi Sains Indonesia, 2022)
Technology has cause society to work efficiently and it has also enabled information to be gained easily. Technology has also helped society in information distribution, knowledge distribution and promotion. One of many information technology used for promotion is website. Rumah Retreat Sarasvita (Sarasvita FCJ Center) is a retreat center located in Yogyakarta where previeusly the retreat already has a website to promote their information about retreat and meditation information to citizen. However, the website was developed using old web technology framework which causing not all information can be deliver easily. To solve this problem, the website feature must be improve and other features have to be added periodically. The aim to improve the website is to help more people to find inner peace through the website. The Sarasvita FCJ Center was still actively give us feed back even until the time this article was written for each feature developed causing the website requirement can be easily matched until Sarasvita satisfied of the feature development.